2020
DOI: 10.30699/jambs.28.127.64
|View full text |Cite
|
Sign up to set email alerts
|

Soy Isoflavone Genistein Is a Potential Agent for Metabolic Syndrome Treatment: A Narrative Review

Abstract: Metabolic syndrome has a high prevalence (about 22.4% in adult individuals) in developed countries. Inflammation due to obesity and fat accumulation is the most important factor in the progression of metabolic syndrome. In cells which have a receptor for insulin hormone, inflammatory mediators target the insulin signaling pathway and cause insulin resistance. Peroxisome proliferator-activated receptors are a group of ligand inducible transcription factors, whose activation can improve insulin resistance and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…A variety of phytochemicals in soybeans have been shown to increase sugar absorption and reduce insulin resistance by activating the PI3K/Akt/GLUT4 signaling pathway [ 50 , 51 , 52 ]. A peptide obtained from fermented soybean food has the potential for glucose utilization through the PI3K/Akt/GLUT4 pathway [ 53 ], and it has been demonstrated that TSP can exert biological activity by specifically activating PI3K/Akt.…”
Section: Resultsmentioning
confidence: 99%
“…A variety of phytochemicals in soybeans have been shown to increase sugar absorption and reduce insulin resistance by activating the PI3K/Akt/GLUT4 signaling pathway [ 50 , 51 , 52 ]. A peptide obtained from fermented soybean food has the potential for glucose utilization through the PI3K/Akt/GLUT4 pathway [ 53 ], and it has been demonstrated that TSP can exert biological activity by specifically activating PI3K/Akt.…”
Section: Resultsmentioning
confidence: 99%
“…The underlying mechanisms explained by inducing effect of soy isoflavone on genes involved in fatty acid catabolism such as PPARα, AMPK and very long-chain acyl -CoA dehydrogenase in conjunction with suppressive effects on genes in charge of lipogenesis like SREBP-1c, PPARγ and acetyl-CoA carboxylase 2 in animal models [72][73][74]. Totally, there are several recent studies investigating the effects of soy or soy isoflavones on metabolic syndrome, which have yielded with the positive results [75][76][77]. Overall, in this study soy isoflavones have led to improve MAFLD by positive effects on some markers of metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, genistein has been shown to accelerate the growth of certain ERs and the progression of estrogen-dependent breast cancer. 27 Understanding the potential benefits and complexities of genistein's interactions with ERs is crucial in harnessing its therapeutic potential for cancer prevention and treatment. Further research is warranted to elucidate the precise mechanisms and optimize their use in clinical settings.…”
Section: Genisteinmentioning
confidence: 99%